A numerical study of rotationally symmetric nanofluid flow over a permeable surface using Buongiorno model. (August 2022) - Tahira, Sahreen; Mushtaq, Ammar; Mustafa, M.
This note describes boundary layer development beneath a generalized vortex flow of nanofluid using two-phase Buongiorno model. Vortex motion is characterized by a prescribed tangential flow with velocity proportional tor m, where r is radial coordinate and m denotes the power-law index. Different from previously adopted practice, the diffusion coefficients are not assumed constant here. A similarity solution is proposed, which transforms the constitutive equations into a coupled differential system whose solution is evaluated numerically. Simulations are made by assuming a power-law surface temperature distribution. Two separate situations namely (i) rigid body rotation (m = 1 ) and (ii) potential vortex (m = − 1 ) are carefully assessed. Furthermore, subtle fluid dynamics entities such as resisting wall shear and heat transfer rate are deliberated. Computational results reveal that there is no noticeable change in nanofluid temperature when diffusion coefficients are varied. Though, marked variations in nanoparticle concentration profile are observed whenever diffusion coefficients are varied.